High-speed, inline measurement of protein activity and inactivation processes by supercontinuum attenuation spectroscopy - Koch, Hanna; Eisen, Kristina; Werblinski, Thomas; Perlitz, Julian; Prihoda, Felix; Lee, Geoffrey; Will, Stefan (Analyst, 2019)
Some proteins such as catalase and glutamate dehydrogenase (GDH) are very sensitive to external factors such as irradiation or heat, which may cause inactivation. Since proteins are used in a wide field of applications, the entire activity has to be ensured during the whole process. By default, activity is measured by invasive and offline activity assays. To avoid the need for a time-consuming offline analysis, we developed an optical high-speed measurement technique, which may form the basis for the non-invasive inline control of enzyme processes e.g. in the textile or food industry. The technique is based on attenuation spectroscopy using a supercontinuum laser source in combination with multivariate data analysis, in particular partial least squares regression (PLSR). For verification of the approach, samples treated by various stresses were analyzed in parallel by activity assays and our new method. Applying this technique, we were able to determine the activity in the turbid catalase samples after heat treatment, addition of guanidine-HCl or irradiation with UV light by applying partial least squares regression. Furthermore, we demonstrate that the combination of broadband attenuation spectroscopy and PLSR enables us to determine also the activity of GDH in clear solutions after heat treatment.
CRIS-Team Scopus Importer:2019-11-26